Structural, Morphological and Tensile Study of CdS/Polystyrene (PS) Nanocomposite - Mathur, Vishal; Sharma, Kananbala (Journal of Research Updates in Polymer Science, 2013)
Thick film of CdS/Polystyrene (PS) nanocomposite was synthesized by dispersing nanofiller particles of CdS in PS matrix. The nanostructure of the CdS particles has been ascertained through X-ray Diffraction (XRD) and Transmission Electron Microscopy (TEM). Small angle x-ray scattering analysis has been performed in order to ascertain nanocomposite character of the PS/CdS sample. Scanning Electron Microscopy (SEM) analyses of these samples have been carried out to establish the surface morphology. The Tensile studies of prepared samples have been ascertained through Dynamic Mechanical Analyzer (DMA). This study reveals that the young’s modulus and the toughness of the material are greatly influenced by the existence of interfacial energetic interaction between dispersed CdS nanofiller particles and matrix of PS.